2022
DOI: 10.54905/disssi/v26i128/ms429e2495
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of public awareness towards skin disease in Jouf region, Saudi Arabia

Abstract: Background: In spite of the fact that skin disease is common, to evaluate the public's overall understanding, awareness and knowledge of skin disorders in Saudi Arabia, just one research was carried out. Objective: This study aims to assess public awareness toward dermatologic disorders in Jouf region and to assess prevalence of common dermatologic disorders among Saudi populace.Methodology: This is a cross-sectional study conducted among Saudi general population in Jouf, Saudi Arabia. Adult participants compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Another study by Qadir et al [30] among students revealed that 93.5% of students knew that cellulitis was a bacterial disease, 83.1% knew that it could be treated medically, and 5.1% reported surgical treatment. In Saudi Arabia, no previous studies assessed public awareness of cellulitis, but Alshaalan et al [31] assessed public awareness of skin diseases, and none of them reported cellulitis as one of the skin-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Qadir et al [30] among students revealed that 93.5% of students knew that cellulitis was a bacterial disease, 83.1% knew that it could be treated medically, and 5.1% reported surgical treatment. In Saudi Arabia, no previous studies assessed public awareness of cellulitis, but Alshaalan et al [31] assessed public awareness of skin diseases, and none of them reported cellulitis as one of the skin-related diseases.…”
Section: Discussionmentioning
confidence: 99%